Serum C-reactive protein levels in severe and very severe pneumonia in children - Dewi, Ni Putu Sucita Wahyu; Purniti, Putu Siadi; Naning, Roni (Paediatrica Indonesiana, 2012)
Background Pneumonia is a major cause of death in children from developing countries. It is difficult to assess pneumonia severity if clinical symptoms of pneumonia are unclear, co-morbidities occur simultaneously, or there is an absence of consolidation or infiltrates on chest radiograph. Examination of C-reactive protein (CRP) levels can help to determine the severity of pneumonia. Objective To compare serum CRP levels in severe and very severe pneumonia cases. Methods This was a cross-sectional study on pediatric patients aged> 28 days up to 60 months v.ith a diagnosis of severe or very severe pneumonia. Subjects were hospitalized at the Department of Child Health, Udayana University Medical SchooliSanglah Hospital, Denpasar from May 2010 to January 2011. There were 30 subjects in each group, severe or very severe pneumonia. Data were analyzed using Mann-Whitney and ANCOVA tests with statistical significance set at P < 0.05. Results There were significant differences in median serum CRP levels in the severe and very severe pneumonia groups. The very severe pneumonia group had a median CRP level of 54.75 mgiL (lQrange 0.22 to 216.00) and the severe pneumonia group had a median CRP level ofl6.06 mgiL (IQ range 0.97 to 89.35). Serum CRP levels were influenced by the severity of pneumonia (P = 0.002) and the timing of the CRP examination (P = 0.001). Conclusion Subjects with very severe pneumonia had significantly higher median CRP level compared to that of subjects with severe pneumonia. [Paediatr Indones. 2012;52:161A].